Mobile, Population-wide, Hybrid HIV Testing Strategy Increases Number of Children Tested in Rural Kenya and Uganda. Issue 12 (December 2018) - Ayieko, James; Chamie, Gabriel; Balzer, Laura; Kwarisiima, Dalsone; Kabami, Jane; Sang, Norton; Cohen, Craig R.; Bukusi, Elizabeth A.; Clark, Tamara D.; Plenty, Albert; Charlebois, Edwin D.; Petersen, Maya; et al.
Abstract : Efficient ways to identify children with HIV in the context of universal test-and-treat policies are needed. We evaluated a hybrid testing strategy combining mobile community and home-based HIV testing in 87, 700 children across 32 rural communities in 2 East African countries. This approach resulted in 81% testing coverage of at-risk children and doubled the number of children diagnosed with HIV.